The Implementation of Problem-Based Learning to Enhance Critical Thinking Skills in Solving Contextual Mathematics Problems - Cahyani, Vionita Fitri; Setyaningsih, Rini (Lombok Institute, 2024)
This study aims to improve students' critical thinking skills in addressing contextual mathematical problems by implementing the Problem-Based Learning (PBL) model in Grade X at SMA Muhammadiyah 3 Surakarta. Using a classroom action research approach with two cycles, data collection included learning observations and critical thinking skills tests. The findings indicate that the implementation of the PBL model effectively enhances students' critical thinking skills in solving contextual mathematical problems. This is evidenced by an increase in students' critical thinking test scores from Cycle I to Cycle II. Furthermore, learning observations revealed improvements in students' engagement, enthusiasm, and proficiency in analyzing and solving contextual mathematics problems. This study underscores the importance for mathematics educators to integrate the PBL model into their teaching practices to enhance students' critical thinking skills. The PBL model has been proven effective in fostering student motivation, increasing participation in learning activities, and cultivating critical thinking skills.